KEARIFAN LOKAL DALAM PENGELOLAAN HUTAN DI DESA SERDANG KECAMATAN BARUSJAHE, KABUPATEN KARO - Karmila Br Ginting; Agus Purwoko; Junjungan Simanjuntak (Program studi Kehutanan USU, 2015)
Management of forest resources is strongly influenced by local knowledge possessed the community to prevent the adverse effects on forests. This study was conducted to inventory of local knowledge related to trust or/and abstinence , ethics and rules, techniques and technologies, as well as the practices and traditions of forest management / land undertaken by the community in building and managing forests in Serdang village, sub-district of Barusjahe, Karo. This research was conducted in the village of Serdang District of Barusjahe , Karo in June to July 2014 The method used was a survey through interviews with respondents using questionnaires and direct observation and then the data is processed by descriptive qualitative method. The results showed that the forms of local knowledge is still contained in Serdang village that can support forest management such as trust and/or customary restrictions such as the implementation of such ceremonial rites and ceremonies rebu rebu of year work, beliefs about village guards called